CHEMICAL AND ORGANOLEPTIC QUALITY CHARACTERISTIC OF SNACK BARS WITH THE ADDITION CONCENTRATION OF SOYBEAN PULP (Glycine max L.) AND MARGARINE - Yudo, Wandoko Sungkowo; Kurnia Hartati, Fadjar; Handarini, Kejora (Fakultas Sains Terapan Universitas Suryakancana, 2024)
Snack bar is a ready-to-eat product in the form of bar that contains good nutrients for the body which if viewed functionally can be used as emergency food consumption. Soybean pulp (Glycine max L.) contains high nutrients that are 28.36% protein, 7.6% crude fiber, and 5.52% fat. Margarine can be used to make processed products tender. The purpose of this study was to determine the effect and what is the concentration of the addition soybean pulp flour and margarine that produces the best chemical and organoleptic quality of snack bars. This research method uses laboratory experimental methods and Complete Randomized Design (RAL) research design with the addition of soybean pulp concentration (20%, 30%, 40%, 50%) and margarine (40%, 30%, 20%, 10%). Based on the results of fingerprint analysis (ANSIRA) using statistical product and service solution (SPSS), the addition of different concentrations of soybean pulp flour and margarine has a significant effect on the water content and protein content of snack bars, has a very real effect on fat content, fiber content, taste, color, and tenderness of snack bars, and there is no real effect on the aroma of snack bars. The determination the best results using the effectiveness test showed that snack bar treatment (T2M2) was the best treatment with yield value (NH) of 0.61% with parameter criteria were protein content of 17.43%, crude fiber content of 4.37%, fat content of 30.83%, crude fiber content of 4.37%, taste 4.1 (like), tenderness 4 (like), color 4 (like), and smell 4 (like).